La politique britannique d’aide à l’innovation : pour une recherche scientifique d’excellence - Marie-Claude Esposito (Revue LISA, 2006)
After justifying the role played by the government in the financing of R&D and investigating the link between innovation, productivity and economic growth, this article deals with the research and innovation policies under Tony Blair. It focuses on the financing of public research institutions whose objective is to ensure that the British economy becomes a knowledge-based economy with increased productivity and economic growth. Since 1997 there has been a strong increase in public funding for the best institutions especially in “project” type funding.